APLIKASI PEMBELAJARAN BAHASA KOREA UNTUK ANAK-ANAK BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract Computer has did much in progression of technology, especially developed to be used for an application that has many functions. Multimedia is one of representation an object by using the computer as the main medium. The purpose of this study to make learning applications and the Korean language and Hangul for the children that is easy to remember. The analysis was done to determine the specifications of Korean language conversation system to fit requirements. Implementation of systems utilizing Eclipse, Android Development Tool (ADT), System Development Kit (SDK), and Java Script. The resulting system was tested with two methods, Black Box Test and quisioner. The results of this study is an application of learning Korean language and Hangeul based on Android. From the results of testing the application system, can be concluded that learning the Korean alphabet or Hangeul was very easy because the program was given a sample image, and how to read, meaning in the Indonesian language, and voice read the Korean alphabet (Hangul) with the correct pronunciation, so it is very easy to learn.Keywords : Korea Language, Hangul, Android , Eclipse